2009
DOI: 10.1148/radiol.2503080474
|View full text |Cite
|
Sign up to set email alerts
|

Modic Changes on MR Images as Studied with Provocative Diskography: Clinical Relevance—A Retrospective Study of 2457 Disks

Abstract: Type 1 signal intensity changes on MR images have a high positive predictive value in the identification of a pain generator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 14 publications
3
85
0
Order By: Relevance
“…Positive associations between MCs and LBP were found with odds ratios (ORs) ranging from 2 to 20. More recently, three additional studies [20,27,32] reported similar findings, in which ORs for this association were 5, 9 and 28.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Positive associations between MCs and LBP were found with odds ratios (ORs) ranging from 2 to 20. More recently, three additional studies [20,27,32] reported similar findings, in which ORs for this association were 5, 9 and 28.…”
Section: Introductionmentioning
confidence: 57%
“…One of these studies [32] reported a higher positive predictive value for pain generation with discography for MCs Type I (0.81) than for MCs Type II or III (0.64 and 0.57, respectively). In a non-clinical population, Kjaer et al [15] found that analysing MCs Type I separately from the other types increased the strength of the association between MCs and LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Positive associations between MCs and LBP were found with odds ratios (ORs) ranging from 2 to 20 [9]. More recently, three additional studies [10-12] reported similar findings, in which ORs for the association were 5, 9 and 28. Although believed to be associated with disc degeneration, the precise etiology of MCs is unknown.…”
Section: Introductionmentioning
confidence: 83%
“…10 It has been shown that there is a significant correlation between Modic changes and pain provocation at discography, suggesting that they can be a predictive sign of low back pain. 11,12 In several longitudinal studies Modic changes have been shown to vary with the passage of time. 13,14 Hutton, Bayer and Powell 14 found that, of 36 endplates with Modic type 1 changes in the first MRI study, 18 remained the same, 13 progressed to type 2, three progressed to type 3, and two became normal, at a mean follow-up of 1.9 years.…”
mentioning
confidence: 99%